The Role Of Discounts And Promotions In Enhancing Consumer Loyalty - Kartomo, Thomas (Sapta Arga Nusantara, 2024)
Consumer loyalty is a critical aspect of business sustainability and competitive success. Companies often implement discounts and promotions as strategies to attract new customers and retain existing ones. This article aims to explore the role of discounts and promotions in enhancing consumer loyalty through a qualitative approach. Data was collected through in-depth interviews with consumers and case studies of several companies actively applying discount and promotional strategies. The findings indicate that discounts and promotions positively impact consumer loyalty, particularly by strengthening emotional attachment and the desire to return for future transactions. However, the effectiveness of these strategies depends on several factors, including the frequency of promotions, relevance to consumer needs, and the perceived value. Additionally, the study found that loyalty developed through discounts and promotions is often temporary and requires follow-up strategies to sustain consumer commitment to the brand. This research provides insights for companies on the importance of designing sustainable and relevant discount and promotional programs for consumers. By gaining a deeper understanding of the factors influencing loyalty, companies can improve customer experiences while maintaining a competitive advantage in the market.